455 Washington Street, ca. 1925 - Boston Globe (Tufts Archival Research Center, 2005)
Street-level view north-northwest of 455 Washington Street, located between Winter Street to the east-northeast and Temple Place to the west-southwest. Signage adorns the facade of the building, which faces south-southeast. Commercial products are displayed in the storefront windows, and pedestrians are included in the photograph. Image is reversed Photographs